2019
DOI: 10.1093/jisesa/iez017
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Conundrum: At-risk Bumble Bees (Bombus spp.) Show Preference for Invasive Tufted Vetch (Vicia cracca) While Foraging in Protected Areas

Abstract: In recent decades, some bumble bee species have declined, including in North America. Declines have been reported in species of bumble bees historically present in Ontario, including: yellow bumble bee (Bombus fervidus) (Fabricus, 1798), American bumble bee (Bombus pensylvanicus) (DeGeer, 1773), and yellow-banded bumble bee (Bombus terricola) (Kirby, 1837). Threats contributing to bumble bee population declines include: land-use changes, habitat loss, climate change, pathogen spillover, and pesticide use. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, although B. pensylvanicus was the bee species with the most observed unique plant species interactions in an Illinois study in the late 1800s, it was only observed once, on one plant species a century later at the same area, despite an extensive survey effort and with many of the same plants being in existence (Burkle et al 2013). In our study, we only had information on plant forage for 31 B. pensylvanicus observations, but 71% of those were on Vicia cracca, a non-native species; interestingly, another recent study in southern Ontario found that at-risk Bombus, including B. pensylvancius, showed a preference for this species rather than native species in the same area as more common Bombus did, presenting an interesting conservation dilemma relating to planting of non-native species (Gibson et al 2019). More information about its plant preferences and nest sites will be important to gather to aid in conservation efforts.…”
Section: Discussionmentioning
confidence: 95%
“…However, although B. pensylvanicus was the bee species with the most observed unique plant species interactions in an Illinois study in the late 1800s, it was only observed once, on one plant species a century later at the same area, despite an extensive survey effort and with many of the same plants being in existence (Burkle et al 2013). In our study, we only had information on plant forage for 31 B. pensylvanicus observations, but 71% of those were on Vicia cracca, a non-native species; interestingly, another recent study in southern Ontario found that at-risk Bombus, including B. pensylvancius, showed a preference for this species rather than native species in the same area as more common Bombus did, presenting an interesting conservation dilemma relating to planting of non-native species (Gibson et al 2019). More information about its plant preferences and nest sites will be important to gather to aid in conservation efforts.…”
Section: Discussionmentioning
confidence: 95%
“…Non‐native plants may be used by at‐risk bee species if they can provide adequate nutrition and if there are limited floral options in the landscape (Baldock et al ., 2015, 2019; Harmon‐Threatt & Kremen, 2015). Focusing on which floral resources at‐risk bumble bees prefer (whether they are native or not) is an important conservation concern as there is growing evidence that declining bumble bee species may have narrower diet breadths (Kleijn & Raemakers, 2008; Gibson et al ., 2019; Wood et al ., 2019) This may be especially important to consider in highly disturbed areas where non‐native plant species dominate that are occupied by at‐risk bumble bees. Our results are unable to separate whether the correlation with native or non‐native flowering plant species reflects preferential use of these resources, or if this is simply a reflection of the landscapes where these species exist and is an important avenue of future research.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of native to non‐native flowering plant species was considered as different bumble bee species may preferentially forage on native vs. non‐native plants (Salisbury et al ., 2015; Gibson et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An understanding of habitat requirements is also important for ensuring the long‐term stability of currently stable populations. Bumble bee habitat must include sites for overwintering, nesting, and foraging and as all of these may differ among species, a detailed understanding of the habitat preferences of individual species is important in conservation management (Gibson et al 2019; Lanterman et al 2019; Liczner & Colla 2019; Wood et al 2019).…”
Section: Introductionmentioning
confidence: 99%